On the issue of classification of media research - Tereschenko, Maria S. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article deals with the approaches to the classification of media research at the present stage of their development. Using the Lasswell’s base communication model, one can distinguish research classes in accordance with their subject area: communicator, messages, communication channels, audience, and communication effects researches. However, this approach does not take into account the relationship between its different components and their relationship. The author also proposes to classify media research on the basis of requests that may come from specific social fields interacting with the media space. This approach, in view of the fundamental understanding of the intersection and interweaving of various social fields, makes it possible to explain both the multitasking of media research and the growing need for an interdisciplinary approach to understanding media research. Classifications by type of media and by methods of collecting and analyzing data are also provided. The article provides the author’s definition of media research.
Keywords: media research; research methods; interdisciplinary approach; social field; media space; basic communication model; media